Investigation of Oxidation Rate Relationship Between Fatty Acid Contents of St. John’s Wort (Hypericum perforatum) Oil and Nettle (Urtica dioica) Seed Oil - Temel Kan Bakır (Turkish Journal of Agriculture: Food Science and Technology, 2018)
Vegetable extract oils are now widely used in health, cosmetics and food fields. The oxidation rates of these industrial oils are closely related to their chemical composition. In this study, fatty acid contents of St. John’s Wort (Hypericum perforatum) oil and Nettle seed (Urtica dioica) oil were investigated by gas chromatography (GS-MS) and the effects on lipid peroxidation time were tried to be related. The peroxidation of oil emulsions was carried out at in a ventilated incubation environment 37°C and pH 7. Pseudo first order constants of primer oxidation products (hydroperoxides) were calculated by Fe (III) SCN method and they found for St. John’s Wort oil and Nettle seed oil, (2.05±0.23)×10-1 and (6.64±0.54)×10-1 hour-1,respectively. This study was conducted by showed that the oxidation rates of St. John’s Wort and Nettle seed oils are closely related to the chemical composition as well as the saturation ratings of fatty acids.